2013
DOI: 10.1021/ef400534f
|View full text |Cite
|
Sign up to set email alerts
|

In Situ FTIR Study of Real-Time Changes of Active Groups during Oxygen-Free Reaction of Coal

Abstract: The distribution of functional groups in two different rank coal samples and their real-time changes during the oxygen-free reaction of coal were tested. An in situ FTIR system was designed to test the real-time changes of functional groups during coal reaction. The real-time changes of aliphatic hydrocarbon groups and oxygen-containing groups were analyzed using the in situ FTIR method. The results show that the distribution of functional groups and their changes are various for different ranks of coals. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(29 citation statements)
references
References 51 publications
0
29
0
Order By: Relevance
“…It has been confirmed that the hydroxyl group is one of the main oxygen-containing groups and its basic characteristic parameters in the structure are almost the same in different ranks of coal. [33][34][35][36][37][38] Coal ranks affect the quantity of active groups existing in coal. The quantities of active groups in low-rank coals are usually larger than those in high-rank ones.…”
Section: Computational Objectmentioning
confidence: 99%
“…It has been confirmed that the hydroxyl group is one of the main oxygen-containing groups and its basic characteristic parameters in the structure are almost the same in different ranks of coal. [33][34][35][36][37][38] Coal ranks affect the quantity of active groups existing in coal. The quantities of active groups in low-rank coals are usually larger than those in high-rank ones.…”
Section: Computational Objectmentioning
confidence: 99%
“…[24,25] Here we will only describe it in short. The main part in the in situ FT-IR system includes an in situ reaction chamber, a gas providing tube, and a programmed heater.…”
Section: The In Situ Ft-ir Systemmentioning
confidence: 99%
“…In consideration of this situation, an in situ FT-IR system of infrared spectrogram was used to test the micro changes during coal reaction at low temperatures. [24,25] Using the in situ FT-IR, the real-time changes of different functional groups during coal reaction under different atmospheres can be obtained exactly.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the low-temperature oxidation of coal is closely related to the type of coal. The difference in the tendency of the spontaneous combustion of different coal types is mainly reflected by the content and occurrence of active groups and inherent oxygen-containing species (Kaji et al, 1985;Qi et al, 2013;Yuan and Smith, 2008).…”
Section: Introductionmentioning
confidence: 99%